Cognitive task performance in sitting and standing: A pilot study - Niedzielska Ewa; Guszkowska Monika; Mikicin Mirosław (Sciendo, 2023)
Study aim: The aims of this study were to compare the effectiveness of performing tasks involving different cognitive functions in sitting versus standing positions and to assess the perceived workload. Standing or moving at work increases energy expenditure and brings health benefits while lowering the risk of diseases related to physical inactivity. The question arises whether this occurs at the expense of the effectiveness of professional activities.